2013
DOI: 10.1063/1.4816371
|View full text |Cite
|
Sign up to set email alerts
|

Structures, energies, and bonding in the water heptamer

Abstract: In this paper we report the geometries and properties of 38 distinct geometrical motifs located on the B3LYP/6-31+G(d), MP2/6-311++G(d, p) potential energy surfaces of the water heptamer. Binding energies of up to 45 kcal/mol are calculated. All motifs fall within 10 kcal/mol of the most stable conformation, with at least 13 structural patterns located no more than 3 kcal/mol above, leading to a very complex potential energy surface, populated by a multitude of motifs each one allowing large numbers of conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 42 publications
3
38
1
Order By: Relevance
“…High‐level ab initio and DFT computations on molecular clusters face a tremendous challenge in producing accurate potential energy surfaces (PESs) for intermolecular interactions owing to the exponential dependency of the number of local minima on the number of molecules . In most cases, chemical intuition is the weapon of choice to guess the best candidates.…”
Section: Introductionmentioning
confidence: 99%
“…High‐level ab initio and DFT computations on molecular clusters face a tremendous challenge in producing accurate potential energy surfaces (PESs) for intermolecular interactions owing to the exponential dependency of the number of local minima on the number of molecules . In most cases, chemical intuition is the weapon of choice to guess the best candidates.…”
Section: Introductionmentioning
confidence: 99%
“…4,33,36,41,43,45, The Møller-Plesset second-order (MP2) perturbation theory has mainly been employed, but some scarce results at the Coupled Cluster Singles, Doubles, and perturbative Triples [CCSD(T)] can also be found. 45,50,56,[62][63][64]74,76 Some studies examining several series of water clusters have also appeared. 4,45,[56][57][58][59]70 Day et al studied the even-membered clusters from six to twenty water molecules by MP2 using a double-zeta basis set in 2000 and also reported CCSD(T) energies at the MP2 geometries for six hexamer isomers.…”
Section: Introductionmentioning
confidence: 99%
“…50 The binding energy of the water heptamer has been reported at both the MP2 and CCSD(T) theories. Acelas et al 76 studied five different structures at the MP2/6-311++G(d,p) and CCSD(T)/6-311++G(d,p) levels, while Kim et al 54 reported ten different isomers at MP2 with similar quality basis sets. The octamer and endecamer systems have been treated with MP2 by one of us 43 employing as large basis sets as aug-cc-pV5Z.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many types of intermolecular interactions, hydrogen bonding is of particular interest because hydrogen bonds (HBs) are known to be responsible for stabilization of various chemical systems, with direct implications in a wide range of scenarios, from the life‐supporting properties of liquid water to the tertiary structures of biomolecules in charge of storing and replicating genetic information . Although the very nature of hydrogen bonding is not without controversy, several types of HBs are recognized in literature .…”
Section: Introductionmentioning
confidence: 99%